PENGElOlAAN lIM BAH MEDIS PADAT DI RSUD DR. R. SOSODORO DJATIKOESOEMO BOJONEGORO - Putri Nursuma Dewi; Darjati .; Demes Nurmayanti (GEMA LINGKUNGAN KESEHATAN, 2015)
RSUDR. Sosodoro Djatikoesoemo Bojonegoro is a grade B government hospital operating a number of healthfacilities and beds, therefore it generates large amount of solid medical wastes. A preliminary survey foundthat there were some issues, such as that officers did not wear full PPE,plastic bags for medical waste that isnot in accordance with the guidelines were being used, and combustion residue from the incinerator weredirectly dumped into a landfill. The study aimed to describe the management of solid medical wastes in RSUDR. Sosodoro Djatikoesoemo Bojonegoro.This is a descriptive type of study, involving several variables to be researched including the generation,sources and types, amount (weight), temporary storage facility, collection methods, 'transportation,destruction, factors that affect amount of waste generated and factors that support the management of solidmedical waste. Primary data were obtained from through observations, interviews, measurement of theamount (weight) of solid medical waste; as well as relevant secondary data. Presentation of data are mostly inthe form of tabulation and analyzed descriptively with 80% compliance standard.The result showed that solid medical wastes originated from health care activities (infectious wastes, sharps,pathological matters, radioactive, and pharmaceutical wastes). The largest amount turned out to be medicaland infectious wastes (± 139.04 kgs/day) and the smallest amount of waste was pharmaceutical wastes (0.07kgs/day); these are influenced by the number vicitors, the number of patients and number of services seekedand provided. Medical waste management made a score of 73.9% (below standard) and smallest percentageswere found in the organizational factors, manpower, equipments and record keeping, costs and budgets,regulations and legal foundation.The study concluded that RSUD R. Sosodoro Djatikoesoemo Bojonegoro is below standard (73.9%). TheHospital was adviced to treat combustion ashes before disposal to landfill, conduct monitoring of toxicchemicals, to sort medical solid wastes according to its type, replacing waste bins according to therequirements, use proper color plastic bags in accordance with the guidelines.